Noninvasive hemoglobin altitude adjustment in Guatemala children - Odeniran, Oluwasanmi Moses (Kansas State University, 2024)
Background: The Anemocheck app, designed for convenient and accessible noninvasive Hb measurement, has tremendous potential in a variety of settings. However, there is little research on its accuracy and utility in different settings like at different altitude levels. Due to the body's natural adaptation of increasing hemoglobin (Hb) levels in response to low oxygen at high altitudes, interpreting Hb test results can be challenging for healthcare professionals, especially when the values fall near the reference range limits. This can make diagnosing anemia or polycythemia difficult. Objective: To determine the accuracy and precision of the Anemocheck app after using different altitude adjustments compared to traditional hemoglobin measurement. Methods: This study was conducted between May and July 2023 in four locations in Guatemala and involved data from 79 children aged 5 to 83 months. Both the Anemocheck app and traditional hemoglobin measurement methods were available for 39 children, the traditional hemoglobin measurements for 40 children could not obtained. The hemoglobin level was measured traditionally in La Asuncion Laboratorio, a laboratory in Sololá, Guatemala using a Mindray BC-5000 automated hematology analyzer. We employed hemoglobin (Hb) adjustment formulas proposed by various researchers to establish thresholds for categorizing Hb measurements as anemic or non-anemic. Additionally, adjustment values derived from established formulas were applied to measure individual Hb values continuously. A two-tailed t-test was used to assess the reproducibility of the Anemocheck app. All statistical analyses throughout this study adhered to a significance level of p < 0.05. All data analyses were done using Microsoft Office Excel 2024 (Microsoft, Redmond, WA, USA). Results: No significant difference was found between the two app measurements (p = 0.70) or between the app's average and the laboratory test (p = 0.21), indicating good reproducibility and agreement. The app's sensitivity and specificity at the threshold [less than or equal to] 11 were 20% (95% CI, 1% to 70%) and 88% (95% CI, 72% to 96%) respectively. % anemia prevalence increased with altitude (details in Table 2.4). The mean and standard deviation of the unadjusted Hb measurement for the Anemocheck app were 12.35 (1.04g/dL) and 12.34 (0.78g/dL) for elevation <2000m and >2000m respectively. The mean and Standard deviation of the adjusted laboratory measurements were 11.74 (0.73g/dL) and 12.45 (1.08g/dL) for elevation <2000m and >2000m respectively. Conclusion: While the app's measurements were reproducible, Hb levels themselves increased with higher altitude thereby increasing the. percentage prevalence of anemia. This aligns with previous research. Interestingly, our findings showed small difference between Hb levels measured by the app and traditional lab tests. This highlights the need for considering altitude and potentially using region-specific Hb thresholds to define anemia accurately. Overall, our study suggests that interpreting Hb levels and defining anemia require us to consider altitude-specific factors even when the noninvasive Hb measurement method is used.
Keywords: Anemocheck app; Anemia; Hemoglobin measurement; High altitude; Hemoglobin adjustment; Noninvasive Hb measurement